Nutritional biochemistry of the vitamins - Bender, David A. (Cambridge, UK ; New York, N.Y. : Cambridge University Press, 2003)
An authoritative and comprehensive review of our current knowledge of the vitamins, their metabolic functions and the scientific basis for setting recommended intakes for the prevention of deficiency and promotion of optimum health. This book will be a valuable reference for students and specialists alike in the field of nutritional biochemistry.
Cover; Half-title; Title; Copyright; Contents; List of Figures; List of Tables; Preface; ONE The Vitamins; TWO Vitamin A: Retinoids and Carotenoids; THREE Vitamin D; FOUR Vitamin E: Tocopherols and Tocotrienols; FIVE Vitamin K; SIX Vitamin B -- Thiamin; SEVEN Vitamin B -- Riboflavin; EIGHT Niacin; NINE Vitamin B; TEN Folate and Other Pterins and Vitamin B; ELEVEN Biotin (Vitamin H); TWELVE Pantothenic Acid; THIRTEEN Vitamin C (Ascorbic Acid); FOURTEEN Marginal Compounds and Phytonutrients; Bibliography; Index.
"Bibliography": pages 409-462
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Vitamins in human nutrition; Nutrition -- Evaluation; Nutrition -- Requirements; Vitamins -- metabolism; Nutrition Assessment; Nutritional Requirements; Vitamins -- therapeutic use; Vitamines dans l'alimentation humaine; Nutrition -- Évaluation.; Alimentation -- Besoins; HEALTH & FITNESS -- Vitamins; Vitamins -- Metabolism; Nutrition Assessment; Nutritional Requirements; Vitamins -- therapeutic use; Vitamins in human nutrition; Nutrition -- Requirements; Nutrition -- Evaluation; Vitamins in human nutrition; Voedingsmiddelen; Vitaminen; Electronic books; Electronic books